Relationship between serum carotenoids and telomere length in overweight or obese individuals - Wang, Jiang; Xie, Fayi; Zhu, Wan; Ye, Dongmei; Xiao, Yi; Shi, Mengxia; Zeng, Rui; Bian, Jiahui; Xu, Xiao; Chen, Lihuan; Zhu, Aizhang; Zhu, Ke; et al. (Frontiers in Nutrition, 2024)
Background: Previous researches have demonstrated an association between carotenoids and elongated telomeres. Nonetheless, there is scant scientific evidence examining this relationship in individuals who are overweight or obese, a demographic more predisposed to accelerated aging. This study aims to elucidate the correlation between serum carotenoid concentrations and telomere length within this population group.: Data were sourced from the 2001-2002 National Health and Nutrition Examination Survey, encompassing 2,353 overweight or obese participants. The levels of α-carotene, β-carotene (both trans and cis isomers), β-cryptoxanthin, lutein/zeaxanthin, and trans-lycopene were quantified via high-performance liquid chromatography. Telomere length was assessed using quantitative polymerase chain reaction.Results: Following adjustment for potential confounders, telomere length exhibited an increase of 1.83 base pairs (bp) per unit elevation in β-carotene levels (β = 1.83; 95% CI: 0.48, 3.18). Within the fully adjusted model, telomere length incremented by 1.7 bp per unit increase in serum β-carotene among overweight individuals (β = 1.7; 95% CI: 0.1, 3.3), and by 2.6 bp per unit increase among obese individuals (β = 2.6; 95% CI: 4 0.1, 5.0). Furthermore, restricted cubic spline analysis revealed a linear relationship between β-carotene levels and telomere length, whereas a non-linear association was observed between β-cryptoxanthin levels and telomere length.Conclusions: This investigation indicates that higher serum β-carotene concentrations are linked with extended telomere length in overweight and obese populations in the United States. These findings warrant further validation through prospective studies.